ANALISIS PSIKOLOGI SASTRA DALAM NOVEL BILA ESOK IBU TIADA KARYA NUY NAGIGA - Hasanah, Istanul; Malik, Abdul; Dwi Leoni, Tessa; Wahyusari, Ahada; Irawan, Dody; Musliha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the literary psychology aspects found in the novel Bila Esok Ibu Tiada by Nuy Nagiga. The research employed a qualitative approach using a descriptive method. The data source was the novel Bila Esok Ibu Tiada (2024), while the research data consisted of narrative excerpts, dialogues, and characters' actions reflecting literary psychology aspects. Data were collected through reading and note-taking techniques and analyzed by identifying, classifying, interpreting, and describing the data based on the literary psychology approach. The findings reveal that the novel contains three major aspects of literary psychology: characters' thoughts, feelings, and behaviors. These aspects represent the characters' psychological responses to the loss of a mother through changes in their ways of thinking, emotional experiences, and actions in dealing with conflict and the recovery process. The study concludes that the novel not only portrays the experience of family loss but also reflects the complexity of human psychological dynamics and humanitarian values, including love, resilience, and perseverance in coping with grief.